PENGARUH MODEL BELAJAR KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DI KELAS V SD - Yana Agustina; Firman Firman; Desyandri Desyandri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Cooperative learning model that makes students work in groups can solve a problem, one of which is Think Pair Share (TPS). The purpose of using this cooperative learning model was that it enabled students to discuss, assess each other's latest knowledge, and help each other in solving mathematical problems. The purpose of this study was to see the effect of the learning model applied in the experimental class on students' mathematical problem solving abilities. The type of this research was experimental with Quasi Experimental Design. The population of this study were all fifth grade students of SD Kartika I-10 Padang. The technique used for sampling is Saturated Sampling. The sample in this study was class VB students of SD Kartika I-10 Padang as the experimental class and class VA students of SD Kartika I-10 Padang as the control class. The instrument was a problem-solving ability test. The collected data were analyzed by using t test. The results of data analysis obtained tcount=0.87 and ttable=1.681 with db=43(n1+n2 -2=23+22–2=4) and a significant level of 5%. Based on the test, tcount < ttable (0.87<1.68), so H0 was accepted and H1 was rejected with the conclusion that